Preparation, characterization, and in vitro and in vivo investigation of chitosan-coated poly (d,l-lactide-co-glycolide) nanoparticles for intestinal delivery of exendin-4 - Wang M (Dove Medical Press, 2013)
Mengshu Wang,1* Yong Zhang,1* Jiao Feng,1 Tiejun Gu,1 Qingguang Dong,1 Xu Yang,2 Yanan Sun,1 Yongge Wu,1 Yan Chen,1 Wei Kong1 1National Engineering Laboratory for AIDS Vaccine, College of Life Science, Jilin University, Changchun, People’s Republic of China; 2BCHT Biopharm Co, Ltd, Changchun, People’s Republic of China*These authors contributed equally to this workBackground: Exendin-4 is an incretin mimetic agent approved for type 2 diabetes treatment. However, the required frequent injections restrict its clinical application. Here, the potential use of chitosan-coated poly (d,l-lactide-co-glycolide) (CS-PLGA) nanoparticles was investigated for intestinal delivery of exendin-4.Methods and results: Nanoparticles were prepared using a modified water–oil–water (w/o/w) emulsion solvent-evaporation method, followed by coating with chitosan. The physical properties, particle size, and cell toxicity of the nanoparticles were examined. The cellular uptake mechanism and transmembrane permeability were performed in Madin-Darby canine kidney-cell monolayers. Furthermore, in vivo intraduodenal administration of exendin-4-loaded nanoparticles was carried out in rats. The PLGA nanoparticle coating with chitosan led to a significant change in zeta potential, from negative to positive, accompanied by an increase in particle size of ~30 nm. Increases in both the molecular weight and degree of deacetylation of chitosan resulted in an observable increase in zeta potential but no apparent change in the particle size of ~300 nm. Both unmodified PLGA and chitosan-coated nanoparticles showed only slight cytotoxicity. Use of different temperatures and energy depletion suggested that the cellular uptake of both types of nanoparticles was energy-dependent. Further investigation revealed that the uptake of PLGA nanoparticles occurred via caveolin-mediated endocytosis and that of CS-PLGA nanoparticles involved both macropinocytosis and clathrin-mediated endocytosis, as evidenced by using endocytic inhibitors. However, under all conditions, CS-PLGA nanoparticles showed a greater potential to be transported into cells, as shown by flow cytometry and confocal microscopy. Transmembrane permeability analysis showed that unmodified and modified PLGA nanoparticles could improve the transport of exendin-4 by up to 8.9- and 16.5-fold, respectively, consistent with the evaluation in rats.Conclusion: The chitosan-coated nanoparticles have a higher transport potential over both free drug and unmodified particles, providing support for their potential development as a candidate oral delivery agent for exendin-4.Keywords: chitosan, PLGA, intestinal absorption